RAPID: characterizing the response of a burned landscape to an unusual and extreme rain event: pebble counts - Nelson, Peter A.; Brogan, Daniel J. (Colorado State University. Libraries, 2015)
This data package was produced by researchers working within the Civil and Environmental Engineering department. The data include real-time kinematic global positioning system (RTK-GPS) survey data of 19 cross-sections and their corresponding longitudinal profiles, photographs, and rain gauge precipitation data collected in two study watersheds (Skin Gulch and Hill Gulch) before and after the September 2013 storms and floods that affected the Colorado Front Range. Pebble counts were also collected in the vicinity of each cross-section.
Pebble counts: RAPID: characterizing the response of a burned landscape to an unusual and extreme rain event
Zip file includes: Pebble Counts spreadsheet and accompanying photographs for Hill Gulch and Skin Gulch, and ReadMe file.
Skin Gulch and Hill Gulch watersheds are located within the 2012 High Park Fire just west of Fort Collins, Colorado (High Park Fire overview map).
Pebble counts were performed in Hill Gulch over the dates of June 19, 2013; July 6, 2013; and February 28, 2014. Pebble counts were performed in Skin Gulch over the dates of June 12, 2013; June 19, 2013; June 25, 2013; and March 5, 2014.
Department of Civil and Environmental Engineering
Keywords: flood; survey; geomorphology; topography; wildfire; erosion; precipitation